Post-traumatic growth in oncological patients during the COVID-19 pandemic - Letizia Lafuenti; Loredana Dinapoli; Ludovica Mastrilli; Vezio Savoia; Marinella Linardos; Riccardo Masetti; Giampaolo Tortora; Vincenzo Valentini; Giovanni Scambia; Daniela P. R. Chieffo (Health Psychology Report, 2023)
Background Post-traumatic growth (PTG) is defined as “positive psychological change experienced as a result of the struggle with high-ly challenging life circumstances”. Diagnosis of cancer leads to many psychological challenges. The recent pandemic forced oncological patients to face other multiple stressors. Resilience is a target of interest for PTG. The aim of this study is to analyze relationships between cancer trauma, COVID-19 pandemic stress, PTG and resilience over time.